PELAKSANAAN PENGELOLAAN HOMESTAY DI DESA LUBUK KEMBANG BUNGA KAWASAN EKO WISATA TESSO NILO KABUPATEN PELALAWAN PROVINSI RIAU - Aminudin, Ali Ria; Arief, Andi M Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aims to determine how the Homestay Management Implementation in the village of Lubuk kembang Bunga Kawasasn Ecotourism Tesso Nilo Pelalawan Riau Province.With this study research method that I use is a qualitative method, in which researchers attempted to describe the actual condition or state by collecting data and information in the field and explain in narrative form without test hypotheses or make predictions before, while the data collection techniques in this research using observation , interviews, and documentation.Based on the results of the research that has been done, Execution Management Homestay already managed properly and the facilities on offer already meet the standards of homestay.Keywords: Management Homestay, Tesso Nilo National Park.